EXPLORING THE NEXUS OF TOURISM DEVELOPMENT, COMMUNITY PERCEPTIONS, AND SUSTAINABILITY IN PROTECTED AREAS - Obradović Strålman , Sanja; Milentijević, Nikola (Bulletin of Natural Sciences Research, 2025)
Sustainable tourism integrates economic, social, and environmental aspects of sustainability. This study investigates the local community’s perceptions of tourism development impacts and factors influencing support for sustainable tourism and destination sustainability within Stara Planina Nature Park. Using a Structural Equation Modeling (SEM) approach, using multiple hypothesized relationships across key dimensions, including economic, environmental, social, and infrastructural impacts are examined. The findings highlight the importance of socio-cultural factors in fostering support, while also recognizing the negative impact of environmental and infrastructural concerns. Socio-cultural impacts significantly and positively influenced support for sustainable tourism and destination initiatives, highlighting the role of cultural exchange, tradition preservation, and community identity in garnering local support. These findings align with previous studies, emphasizing the importance of perceived socio-cultural benefits in fostering community backing for tourism development. Effective STD management requires the active involvement of local stakeholders to ensure alignment with local values and environmental goals. Policymakers should focus on enhancing socio-cultural benefits, addressing infrastructural challenges, and effectively communicating economic advantages. Limitations of the study include its cross-sectional design, suggesting the need for longitudinal research to better understand the evolving impact of tourism.
Keywords: Sustainable tourism; Destination sustainability; Local community; Tourism impact; Residents’ support; Protected areas